Association between mean platelet volume and Microalbuminuria in Type 2 Diabetes Mellitus Patients - Joena M Virgin; Prabhuswamy K M (International Journal of Medical Research and Review, 2017)
Background: Type 2 DM is characterized by increased platelets activation, hence platelet functional markers like the mean platelet volume (MPV) can play a vital role in identifying subjects at high risk of developing microvascular complications.Objectives: To study the association between mean platelet volume and micro albuminuria and to analyse factors associated with MPV in patients with Type 2 diabetes mellitus.Materials & Methods: A cross sectional study was conducted in the department of internal medicine, Velammal medical college and hospital, between June 2016 and December 2016. Subjects with DM, with age > 20 years were included. Latex Turbidimetric method was used to assess urine micro albumin.Results: A total of 269 diabetic patients with mean duration of disease of 4.84 years were included. There was a moderate, statistically significant positive correlation between HbA1 C level and Mean platelet volume (PCC=-0.198, p value 0.001). The other factors had shown no statistically significant correlation with MPV. There was a Statistically significant mild negative correlation between serum uric acid and MPV (PCC= -0.196, p value 0.001). The mean MPV in people with low and high Urine micro albumin was 7.716 ± 0.876 and 7.705 ± 0.890 respectively, and the difference was statistically not significant.Conclusion: Poor glycaemic control may lead to higher MPV in diabetic population. Very minimal and statistically non-significant difference was observed in mean MPV value between subjects with high micro albuminuria and low micro albuminuria.